'It is not entirely healthy.' A qualitative study into public appraisals of uncertain risks of chemical substances in food. (February 2020) - Jansen, Tom; Claassen, Liesbeth; van Kamp, Irene; Timmermans, Daniëlle RM
For some chemical substances in food, scientific uncertainty prevents definitive statements about the presence of risk for human health. In this qualitative study, we explored the public's understanding and risk appraisal of these substances. During semi-structured interviews, participants from the public were presented with inconclusive risk information about either a food additive or one of two food contaminants. Findings show that interviewees had no prior knowledge and constructed their risk appraisal on the spot. Results suggest that generic and case specific beliefs and inferences affect understanding and appraisal. Respondents' interpretations of the risk messages used in this study were often not in line with what the message intended to convey. In addition, specific use of scientific jargon was associated with increased risk. In general, respondents were more apprehensive about the presence of the chemical in food than that they were worried about the chance of experiencing health effects.